Hubungan Fungsi Keluarga dengan Kecerdasan Emosional Remaja Sekolah Menengah Pertama - Dhiya Sahira; Yarmis Syukur (Lembaga Yasin AlSys, 2026)
Emotional intelligence is an important aspect of adolescents’ lives, including in the learning process of junior high school students, and one of its determining factors is the extent to which family functions are fulfilled. This study aimed to describe family function and adolescents’ emotional intelligence and to examine the relationship between family function and the emotional intelligence of junior high school students. The research employed a quantitative correlational approach, with a population comprising all 888 students of SMP Negeri 29 Padang and a sample of 273 students selected using proportional random sampling. The research instruments consisted of a family function scale and an emotional intelligence scale using a Likert-type model. Data were analyzed using descriptive statistics and Pearson product–moment correlation. The results showed that both family function and adolescents’ emotional intelligence were generally in the moderate category. The correlation test indicated a positive and significant relationship between family function and adolescents’ emotional intelligence, with a correlation coefficient of 0.782 at a significance level of 0.000, suggesting that the better the family function, the higher the adolescents’ emotional intelligence. These findings underscore the importance of the family’s role in supporting adolescents’ emotional development and provide a basis for developing guidance and counseling services that optimally involve families in the student support process.